ADMINISTRATION ON AGING. GLOBAL COMPARISON OF FORMAL AND INFORMAL CAREGIVING - Batiashvili, Gogi; Gerzmava, Otar (European Scientific Journal, ESJ, 2014)
Countries in regions of the world are managing aging populations differently, but each country offers lessons to be learned. Countries used as examples include Germany, Australia, Japan, Uruguay, Kenya, Hungary, and the United States. All of these countries have some type of formal, informal, or both systems in place to care for older persons. These countries, among others throughout the world, will have to confront decreasing familial caregivers together with longer life expectancy. Other issues to consider include policy formation, resource allocation, health care, and diversity.